Awareness and Implementation of Philippine Digital Workforce Competitiveness Act by Philippine LGUs - Sanier, Diana Mae; Tuble, Ruvy (Journal of Interdisciplinary Perspectives, 2025)
This study assessed the awareness, extent of implementation, challenges encountered, and perceived benefits associated with the Philippine Digital Workforce Competitiveness Act of 2022 (RA 11927) in a Local Government Unit (LGU) in Negros Occidental. Utilizing a descriptive-correlational research design, data were gathered from 109 implementers using a validated and reliable questionnaire. Findings revealed high levels of awareness and implementation, particularly among municipal-level implementers and those with 11 to 15 years of service. Among the Act’s components, Digital Careers was the most extensively implemented. Significant challenges included limited funding, inadequate leadership support, insufficient training opportunities, and weak digital infrastructure. Despite these barriers, implementers perceived notable benefits, including enhanced public service delivery and improved digital literacy among constituents. A strong positive correlation was established between awareness and implementation, although no significant differences emerged across demographic variables. The study contributes to both theory and practice by highlighting critical enablers and bottlenecks in digital policy execution at the local level. These insights can guide policymakers in designing more inclusive, well-resourced, and sustainable digital workforce initiatives nationwide.